Given;
There are given that the polynomial:
![P(x)=-2x^4-4x^3+4x^2-7](https://img.qammunity.org/2023/formulas/mathematics/college/zi73adupfguouglg7sswjg95hbi1di68fy.png)
Step-by-step explanation:
To find the quotient and remainder, we need to find the value of P(-2):
Then,
![\begin{gathered} P(x)=-2x^(4)-4x^(3)+4x^(2)-7 \\ P(-2)=-2(-2)^4-4(-2)^3+4(-2)^2-7 \\ P(-2)=-2(16)-4(-8)+4(4)-7 \\ P(-2)=-32+32+16-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uw4xdpv6n39sbn5nzay7p3i3hmrpxsro80.png)
Then,
![\begin{gathered} P(-2)=-32+32+16-7 \\ P(-2)=16-7 \\ P(-2)=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/12to58hn0hdbbqkfbo9hen3s897zblzb2m.png)
So, the remainder is 9.
Now,
For the quotient:
Divide the given polynomial by (x+2):
So,
![(-2x^4-4x^3+4x^2-7)/(x+2)=-2x^3+4x-8](https://img.qammunity.org/2023/formulas/mathematics/college/19aj7pewu74vrowohy2q6n84g7w1bz9sxf.png)
Final answer:
Hence, the quotient, remainder, and the value for P(-2) is shown below:
![\begin{gathered} Quotient:--2x^2+4x-8 \\ Remainder:9 \\ P(-2)=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hxapq3ds791w7z8i8mkgzoxmpemoxhjppw.png)